Simultaneous optical, CUTLASS HF radar, and FAST spacecraft observations: signatures of boundary layer processes in the cusp - Oksavik, K.; Søraas, F.; Moen, J.; Pfaff, R.; Davies, J. A.; Lester, M. (HAL CCSD, 2004)
International audience In this paper we discuss counterstreaming electrons, electric field turbulence, HF radar spectral width enhancements, and field-aligned currents in the southward IMF cusp region. Electric field and particle observations from the FAST spacecraft are compared with CUTLASS Finland spectral width enhancements and ground-based optical data from Svalbard during a meridional crossing of the cusp. The observed 630nm rayed arc (Type-1 cusp aurora) is associated with stepped cusp ion signatures. Simultaneous counterstreaming low-energy electrons on open magnetic field lines lead us to propose that such electrons may be an important source for rayed red arcs through pitch angle scattering in collisions with the upper atmosphere. The observed particle precipitation and electric field turbulence are found to be nearly collocated with the equatorward edge of the optical cusp, in a region where CUTLASS Finland also observed enhanced spectral width. The electric field turbulence is observed to extend far poleward of the optical cusp. The broad-band electric field turbulence corresponds to spatial scale lengths down to 5m. Therefore, we suggest that electric field irregularities are directly responsible for the formation of HF radar backscatter targets and may also explain the observed wide spectra. FAST also encountered two narrow highly structured field-aligned current pairs flowing near the edges of cusp ion steps. Key words. Ionosphere (electric fields and currents). Magnetosphere physics (magnetopause, cusp, and boundary layers; auroral phenomena)